2016
DOI: 10.1007/s11121-015-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Evaluation of a Risk-Scoring Tool to Predict Participant Attrition in a Lifestyle Intervention Project

Abstract: Participant attrition in clinical trials and community-based interventions is a serious, common, and costly problem. In order to develop a simple predictive scoring system that can quantify the risk of participant attrition in a lifestyle intervention project, we analyzed data from the Special Diabetes Program for Indians Diabetes Prevention Program (SDPI-DP), an evidence-based lifestyle intervention to prevent diabetes in 36 American Indian and Alaska Native communities. SDPI-DP participants were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Female parents outnumbered male parents in this study by 14 to 1, which is the likely cause of the large CI shown in Table 3 . Others have reported that some of these same factors were predictive of premature termination of participation in intervention studies, including illness [ 92 , 164 ], family stress [ 165 ], and being male [ 120 , 164 ], as well as many other factors that were not predictors in this study. For example, predictors of participant completers in other studies associated with behavioral intervention trials that were not predictors in this study include sociodemographic (e.g., household income, level of education, family size, race/ethnicity), parent intrapersonal (e.g., depression, management skills), child intrapersonal (e.g., perceived susceptibility of child to health risk), and family interpersonal (e.g., family support) characteristics, as well as neighborhood conditions [ 22 , 24 , 26 , 33 , 92 , 129 – 134 , 138 , 164 , 166 , 167 ].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Female parents outnumbered male parents in this study by 14 to 1, which is the likely cause of the large CI shown in Table 3 . Others have reported that some of these same factors were predictive of premature termination of participation in intervention studies, including illness [ 92 , 164 ], family stress [ 165 ], and being male [ 120 , 164 ], as well as many other factors that were not predictors in this study. For example, predictors of participant completers in other studies associated with behavioral intervention trials that were not predictors in this study include sociodemographic (e.g., household income, level of education, family size, race/ethnicity), parent intrapersonal (e.g., depression, management skills), child intrapersonal (e.g., perceived susceptibility of child to health risk), and family interpersonal (e.g., family support) characteristics, as well as neighborhood conditions [ 22 , 24 , 26 , 33 , 92 , 129 – 134 , 138 , 164 , 166 , 167 ].…”
Section: Resultsmentioning
confidence: 67%
“…Additionally, this is among the first papers to report recruitment and retention strategies for an online, community-based, parent-driven childhood obesity prevention intervention [ 116 ] and to report a comprehensive, systematic RCT recruitment and retention plan based on services marketing principles. Few studies have expanded the consideration of retention factors beyond sociodemographic characteristics and/or used theoretical underpinnings to guide the selection of retention factors when examining predictors of RCT completers [ 25 , 26 , 92 , 101 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor retention is a problem because longer time spent in weight-loss programs is associated with better weight outcomes ( Jiandani et al, 2016 ); poor retention may distort study findings, likely biasing toward program effectiveness, and require better retention strategies ( Rae et al, 2013 ). Retention in weight-loss programs is generally associated with older age ( Leahey et al, 2010 , Jiandani et al, 2016 , Jiang et al, 2016 , Babatunde et al, 2017 , Burgess et al, 2017 , Leung et al, 2017 , Stoutenberg et al, 2017 , Alexander et al, 2018 , Tomioka et al, 2019 ), though some studies have found no such association ( Moroshko et al, 2011 , Latner and Ciao, 2014 ). Retention rates have been found to be higher among females ( Jiang et al, 2016 ), but also among males ( Burgess et al, 2017 ) or not associated with gender ( Moroshko et al, 2011 , Stoutenberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Retention in weight-loss programs is generally associated with older age ( Leahey et al, 2010 , Jiandani et al, 2016 , Jiang et al, 2016 , Babatunde et al, 2017 , Burgess et al, 2017 , Leung et al, 2017 , Stoutenberg et al, 2017 , Alexander et al, 2018 , Tomioka et al, 2019 ), though some studies have found no such association ( Moroshko et al, 2011 , Latner and Ciao, 2014 ). Retention rates have been found to be higher among females ( Jiang et al, 2016 ), but also among males ( Burgess et al, 2017 ) or not associated with gender ( Moroshko et al, 2011 , Stoutenberg et al, 2017 ). Other common factors associated with retention are initial weight or BMI and initial weight-loss success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation